Hydrocarbons and thermal evolution of the bintuni basin of western papua, assessed by apatite fission track study - Perpustakaan UGM, i-lib ([Yogyakarta] : LPM-UGM Bulaksumur Blok F-1,Yk 55281 Telp (0274)901170-901173 fax(0274)5153911, 2006)
ABSTRACT The present apatite fission track study aimed to assess thermal evolution of sedimentary rock successions, and its implications for the occurrence of hydrocarbons within the Neogene Bintuni basin of western Papua. The basin contains a thick Mesozoic to Recent sequence, which has been gently folded by the Melanesian deformation. Results of apatite fission track analysis show that the Upper Miocene-Pleistocene Steenkool Formation has been heated to paleotemperatures below 85Â°C since deposition. Whereas, the Triassic-Lower Jurassic Tipuma sections have been subjected to paleotemperatures of about 110Â°C. Importantly, these elevated paleotemperatures are concordant with present temperatures, and thus the rocks are now at their maximum temperature today. The exposure of Mesozoic rocks to high paleotemperatures was due principally to Late Cretaceous-Pleistocene burial, which commenced after formation of Jurassic unconformity. However, the deeper sequences within the basin were not buried so deeply, allowing preservation of the reservoir porosity. This scenario agrees well with the recent discovery of â30 tcf reserves of gas in the Tangguh gas province within the Bintuni basin.